2015
DOI: 10.1007/s13197-015-2032-8
|View full text |Cite
|
Sign up to set email alerts
|

Production and evaluation of breakfast cereals from blends of acha and fermented soybean paste (okara)

Abstract: Breakfast cereals was formulated from blends of acha and fermented okara (soybean residue). Acha grains were cleaned, winnowed, washed, dried (at 50°C for 4 h) and milled into flour. Okara was processed from soybean seed through the stepwise procedure of cleaning, soaking, washing, milling and sieving. The residue was divided into five portions, fermented differently for 0, 12, 24, 36, and 48 h and then dried at 50°C for 6 h. Acha flour (UFAC) was milled and blended at 50, 60, 70, 80, 90, 100 % ratio with mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 33 publications
4
21
4
Order By: Relevance
“…These results are in agreement with the findings of Guimarães et al () who reported that fortification of vegetable paste with okara increased its protein (3.04–4.7 g/100 g), lipids (5.6–6.6 g/100 g), fiber (5.79–8.00 g/100 g), and decreased carbohydrate contents (5.86–3.50 g/100 g) as the soy okara concentration increased in the formulations (33.87–50.60 g/100 g). A similar pattern of increased moisture, ash, fat, protein, fiber, and decreased carbohydrate level were also reported by Mbaeyi‐Nwaoha and Uchendu () for okara‐based breakfast cereals and this could be attributed to the higher content of these nutrients in added okara flour than the durum wheat flour. Protein‐enriched okara‐based pasta will be of nutritional importance for the people of developing nations who can hardly afford high‐cost protein‐rich food products.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…These results are in agreement with the findings of Guimarães et al () who reported that fortification of vegetable paste with okara increased its protein (3.04–4.7 g/100 g), lipids (5.6–6.6 g/100 g), fiber (5.79–8.00 g/100 g), and decreased carbohydrate contents (5.86–3.50 g/100 g) as the soy okara concentration increased in the formulations (33.87–50.60 g/100 g). A similar pattern of increased moisture, ash, fat, protein, fiber, and decreased carbohydrate level were also reported by Mbaeyi‐Nwaoha and Uchendu () for okara‐based breakfast cereals and this could be attributed to the higher content of these nutrients in added okara flour than the durum wheat flour. Protein‐enriched okara‐based pasta will be of nutritional importance for the people of developing nations who can hardly afford high‐cost protein‐rich food products.…”
Section: Resultssupporting
confidence: 83%
“…Protein‐enriched okara‐based pasta will be of nutritional importance for the people of developing nations who can hardly afford high‐cost protein‐rich food products. Many studies have suggested that fiber‐rich foods will be useful in regulation of many physiological functions and prevention of disease syndromes of various origins, namely cancer, diabetes, cardiovascular diseases, diverticulosis, and constipation (Mbaeyi‐Nwaoha & Uchendu, ). Energy value of the pasta samples has increased from 385.33 ± 0.36 to 409.89 ± 1.00 kcal/100 g with the addition of soy okara flour in the formulations (0–50 g/100 g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Table 2, it was observed that the mean values for the texture decreased as the addition of mung bean exceed 10% but its addition at this level improved the texture of the breakfast cereal. This is in agreement with the findings of Chukwu and Abdul-kadir (2008) as well as Mbaeyi-Nwaoha and Uchendu (2016).…”
Section: Sensory Scores Of Breakfast Cereal Produced From Acha and Musupporting
confidence: 93%
“…The highest value was observed in sample ABE (13.62mg/100g) while the least value was observed in sample AAA (control). The results obtained were less than the values (188-289mg/100g) recorded for a breakfast cereal made from blends of Acha and fermented Soybean paste (okara) [30]. The results revealed that the phosphorus content of the formulated samples increased with increasing addition of the jackfruit seed flour in the formulation, although the values obtained were less than the US RDA (350-450mg/100g for adults) per day.…”
Section: Mineral Content Of the Breakfast Cerealmentioning
confidence: 57%